Effect of Process Pressure on the Properties of Cu2O Thin Films Deposited by RF Magnetron Sputtering - Junghwan Park; Chang-Sik Son; Young-Guk Son; Donghyun Hwang (Crystals)
Cu2O thin films were deposited on soda-lime glass substrates using RF magnetron sputtering under various process pressures, and their structural, morphological, compositional, and optical properties were investigated. X-ray diffraction (XRD) revealed that the films crystallized in the cubic Cu2O phase, with the highest crystallinity observed at 5 mTorr, as evidenced by the sharp and intense (111) peak. Raman spectroscopy confirmed the predominance of Cu2O vibrational modes across all samples, with improved phase purity and crystallinity at 5 mTorr and 10 mTorr. Field-emission scanning electron microscopy (FE-SEM) showed that the films deposited at 5 mTorr and 10 mTorr exhibited densely packed, well-defined grains, while those at 1 mTorr and 15 mTorr displayed irregular or poorly defined morphologies. X-ray photoelectron spectroscopy (XPS) confirmed the presence of Cu(I) without significant secondary phases, with slight surface oxidation observed at higher pressures. Optical characterization revealed that transmittance increased with pressure, reaching ~90% in the NIR range at 15 mTorr. The optical band gap (Eg) values increased from 2.34 eV at 1 mTorr to 2.43 eV at 15 mTorr with higher process pressure. Cu2O films deposited at 5 mTorr and 10 mTorr exhibited an optimal balance between high transparency and band gap values. These findings highlight the critical role of process pressure in determining the properties of Cu2O thin films and identify 5 mTorr as the optimal deposition condition for achieving high-quality films with superior structural and optical performance.